Neuropharmacology of memory consolidation and reconsolidation: insights on central cholinergic mechanisms - Blake, Mariano Guillermo (2014)
Central cholinergic system is critically involved in all known memory processes. Endogenous acetylcholine release by cholinergic neurons is necessary for modulation of acquisition, encoding, consolidation, reconsolidation, extinction, retrieval and expression. Experiments from our laboratory are mainly focused on elucidating the mechanisms by which acetylcholine modulates memory processes. Blockade of hippocampal alpha-7-nicotinic receptors (α7-nAChRs) with the antagonist methyllycaconitine impairs memory reconsolidation. However, the administration of a α7-nAChR agonist (choline) produce a paradoxical modulation, causing memory enhancement in mice trained with a weak footshock, but memory impairment in animals trained with a strong footshock. All these effects are long-lasting, and depend on the age of the memory trace. This review summarizes and discusses some of our recent findings, particularly regarding the involvement of α7-nAChRs on memory reconsolidation.